GAMBARAN UPAYA IBU DALAM PEMENUHAN KONSUMSI SAYUR DAN BUAH PADA ANAK PRASEKOLAH - Syaputri, Riauni; Anggreny, Yecy; Niriyah, Sekani (Jurnal Cakrawala Promkes, 2019)
The period of growth and development in preschoolers is strongly influenced by the provision of nutrition and food intake, but mothers can not always to fulfil these needs, especially in fulfilling the consumption of vegetables and fruit. This study aims to determine the description of maternal efforts in fulfilling the consumption of vegetables and fruit in preschool children. This research was a quantitative study with a descriptive research design. The study population was all mothers who have preschool children in Public Health Centre â€œPayung Sekaki Pekanbaruâ€. Total sample 192 people, taken by Proportional Random Sampling technique. The process of collecting data using an instrument in the form of a questionnaire. Data were analyzed by the Chi-square test. The results showed that of the 192 respondents most of which are 169 people (88.0%) have adequate eating habits, parenting eating most obtained good parenting patterns that are 191 people (99.5%), feeding practices of most respondents were correct namely 97 people (50.5%), the majority of respondents provide good food namely 190 people (99.0%), and the method of food processing shows that the majority of respondents have processed food properly, namely 145 people (75.5%). Mother's efforts in fulfilling the consumption of vegetables and fruit in preschool children in the work area of Payung Sekaki Health Center are good. It is expected that the public health centre will always provide counselling to the public on the importance of balanced food consumption, one of which is to consume spinach and spinach as well as papaya and bananas which have many benefits for children's growth and development, as well as educating parents to more routinely provide vegetable and fruit intake in children every meal hour.